Difusión de 51 Cr en aleaciones Zr-Sn - Nicolai, Julio Antonio; Migoni, R.; Hojvat de Tendler, Ruth (Comisión Nacional de Energía Atómica; Argentina, 1982)
Fil: Nicolai, Julio Antonio Comisión Nacional de Energía Atómica; Argentina